Book Review: Judit Pál – Vlad Popovici – Andrea Fehér – Ovidiu Emil Iudean (ed.), “Parliamentary elections in Eastern Hungary and Transylvania (1865–1918)”, Berlin, International Verlag der Wissenschaften, 2018 - SZABÓ, Zsolt (Studia Universitatis Babeș-Bolyai Historia, 2022)
As a result of the Covid-19 pandemic, many archives and libraries have closed down, “starving” researchers of their working material. In such cases, we start to truly appreciate digitalized databases, as well as books that can compile sizeable amounts of data, based on a large number of sources, with a good critical apparatus. One such book is entitled “Parliamentary Elections in Eastern Hungary and Transylvania (1865–1918)”, and was edited by Judit Pál, Vlad Popovici, Andrea Fehér and Ovidiu Emil Iudean, the latter three being members of the teaching staff of the Faculty of History and Philosophy of Babeş-Bolyai University, and the former being a researcher at the same university. The volume describes Hungarian parliamentarism, and features a wide variety of information about the elected deputies from Transylvania and Eastern Hungary, including important information about the electoral constituencies, while also offering a critical account of the sources used to create the tables of information.